WASHINGTON REPORT WASHINGTON RELATIONS OFFICE ELECTION OVERVIEW, YEAR-END WRAP-UP, AND OUTLOOK FOR 930000 (Tufts Archival Research Center, 2007)
Report with an overview of elections, a year end wrap up and an outlook for 1993. Includes activities within Congress that have affected Philip Morris, as well as activity anticipated for 1993. Includes issues of: clean indoor air, advertising bans, workplace smoking bans, excise taxes, and federal regulation of tobacco and youth smoking.